Moderating effect of taxpayer perception on the relationship between electronic taxpayer education and turnover tax compliance among SMEs in Eldoret town, Uasin Gishu County - Simiyu, Phiona Bisela (Journal of Accounting, Business and Finance Research, 2024)
Taxpayer education has not best added extraordinary impact on big Small and Medium Enterprises (SMEs) marketplace performances but has also advanced well timed and coherent turnover tax compliance. Previous research has indicated that the turnover tax compliance among the SMEs have remained low. That is attributed to lack of tax compliance by SMEs via tax evasion, moving or briefly shutting down businesses. The study sought to assess the impact of electronic taxpayer education on turnover tax compliance amongst small and medium enterprises in Eldoret Town, Uasin Gishu County. The study was supported via monetary deterrence theory. Explanatory studies design was used focused on 68712 registered small and medium enterprises inside Eldoret town. Systematic sampling changed into used to pick out a sample of 397 SMEs. Questionnaires were used as the main facts series tool. Statistical Program for social sciences software was used to investigate quantitative facts both descriptively and inferentially. Findings from the study indicated that electronic taxpayer education had positive and significant effect on TOTC (Turnover Tax Compliance) of SMEs in Eldoret town (β1 = 0.600, p = 0.000<0.05). With a positive and significant effect of (β4=0.422, p=0.003<0.05), taxpayer perception moderates turnover tax compliance of SMEs in Eldoret town. The study concludes that electronic taxpayer education has a significant effect turnover tax compliance of SMEs in Eldoret town. The study therefore recommends that policy makers should focus on providing tax education programs for SMEs. This is to address the specific needs and challenges faced by SMEs in complying with tax regulations.